Garcinia kola seed ameliorates renal, hepatic, and testicular oxidative damage in streptozotocin-induced diabetic rats (2015)
"Context: In Africa, Garcinia kola Heckel (Guttiferae) seed is commonly recommended in folklore medicine for the treatment of diabetes and its associated complications. Objective: The present study evaluated this traditional claim by mechanistic investigation into the effect of G. kola seed administration on renal, hepatic, and testicular oxidative damage in streptozotocin (STZ)-induced diabetic rats. Materials and methods: Diabetes mellitus was induced in adult male Wistar rats by an intraperitoneal injection of STZ (50 mg/kg). The diabetic rats were thereafter treated orally once per day with G. kola seed (250 mg/kg) and monitored for 14 d. Clinical observations, plasma biochemistry, hormonal profile, oxidative stress indices, sperm characteristics, and histopathological examination of the kidney, liver, and testes were evaluated to monitor treatment-related effects of G. kola seed in STZ-induced diabetic rats. Results and discussion: Garcinia kola seed administration significantly ameliorated hyperglycemia mediated damage by decreasing the blood glucose level (72.8% and 84.6% on the 7th and 14th post-treatment days, respectively), enhancement of the antioxidant system, inhibition of lipid peroxidation, and improving the architecture of the kidney, liver, and testes in STZ-induced diabetic rats. In addition, G. kola seed intervention restored the kidney and liver function biomarkers, the sperm characteristics as well as the plasma levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone, triiodothyronine (T3), and thyroxine (T4) to normal in STZ-induced diabetic rats. Conclusion: The findings from this investigation provide persuasive scientific support for the traditional use of G. kola seed in the treatment of diabetes and its associated complications.